2018
DOI: 10.1016/j.yclnex.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Andrographis paniculata can modulate the ratio of Treg to Th17 cells in atherosclerotic rats

Abstract: s u m m a r yThe purpose of this study is to analyze the effect of Andrographis paniculata (Burm F) in the modulation of naive T cell differentiation and its related cytokines in the rat model of atherosclerosis. Twenty-five male rats were assigned to five study groups, consisting of the control group (normal diet), the atherosclerosis rat group (atherogenic diet), and the atherosclerotic rat group receiving A. paniculata (Burm F) extracts in three doses, there were 0.6 mg/kgBBW (Ather þ AP1 group), 1.2 mg/kgB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Aterosklerosis merupakan kondisi perubahan patologi vaskular yang ditandai dengan peradangan dan plak didinding arteri [1]. Aterosklerosis adalah penyakit arteri progresif yang nantinya dapat berkembang menjadi penyakit jantung dan stroke.…”
Section: Pendahuluanunclassified
“…Aterosklerosis merupakan kondisi perubahan patologi vaskular yang ditandai dengan peradangan dan plak didinding arteri [1]. Aterosklerosis adalah penyakit arteri progresif yang nantinya dapat berkembang menjadi penyakit jantung dan stroke.…”
Section: Pendahuluanunclassified
“…Th17 cells, which are pro-inflammatory mediators that produce IL-17, IL-22 and IL-23, 114 mediate proatherogenic progression. 115,116 Studies have shown that Th17 cell levels increase significantly in atherosclerotic rats, 117 and IL-17 expression (a marker of Th17 cells) is upregulated in patients with atherosclerosis. 118 This effect may be associated with the role of Th17 cells in stabilizing plaques through induced fibrosis.…”
Section: The Role Of T Cells In Atherosclerosis and Calcificationmentioning
confidence: 99%